Effective project management based on performance index - Siti Syafinah Amirah, Salleh (2017)
The problem of delays in the construction industry is a global phenomenon and the construction industry . the goal of all parties involved in construction projects- clients, Project Manager, Engineering Consulatants and Contractors in either the public or private sector is to successfully complete the project on schedule, within planned budget, with the highest quality and in the safest manner. Constrcution projects are frequently influenced by either success indicators that help project parties reach their goal as planned, or delay indicators that stfle or postpone project completion. The prupose of this research is to identify success and delay indicators which can help project parties reach their intended goals with greater efficiency. This research extracted six of the most important success indicators according to the literature and six of the most important delay indicators identified by project parties, and then examined correlations between them to determine which were the most influentiatl in preventing project delays. This research uses a comrehensive literature review to design and conduct a survey to investigate success and delay indicators. A specific survey was contributer to contractors, client, project manager and engineering consultants to examine the most causes delay indicators. A general survey was distributed to examine the correlation between the identified delay indicators and the six most important causes success indicators selected. A consensus of expert opinion using the statistical methos to rank the most needed causes of success indicators for consturction industry especially for the example of project at Cyberjaya.